2015
DOI: 10.1177/0954405414563420
|View full text |Cite
|
Sign up to set email alerts
|

Belt grinding process with force control system for blade of aero-engine

Abstract: In abrasive belt grinding process for surface of blade, elasticity, deformation and abrasive belt wear are major factors affecting the machining stability, efficiency and quality. In order to improve the grinding process and realize optimal grinding, a new controllable and flexible belt grinding mechanism is designed and assembled in a special computer numerical control grinding machine, accompanied with a constant grinding force control system. Based on the analysis of proportional valve and cylinder system i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
10
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 17 publications
(10 citation statements)
references
References 31 publications
0
10
0
Order By: Relevance
“…Some related study has shown that the constant grinding force combined with the optimal process parameters is quite suitable for belt grinding of complex surfaces. 21,22,26,32 In the process of machining, the change of speed v s or v w does not adversely affect the surface of the workpiece while the change of F n will cause impact in the contact area, leaving large marks on the machined surface. The phenomenon of over- and under-cutting of the workpieces can also be avoided by a constant normal force.…”
Section: Constant Force Grindingmentioning
confidence: 99%
See 3 more Smart Citations
“…Some related study has shown that the constant grinding force combined with the optimal process parameters is quite suitable for belt grinding of complex surfaces. 21,22,26,32 In the process of machining, the change of speed v s or v w does not adversely affect the surface of the workpiece while the change of F n will cause impact in the contact area, leaving large marks on the machined surface. The phenomenon of over- and under-cutting of the workpieces can also be avoided by a constant normal force.…”
Section: Constant Force Grindingmentioning
confidence: 99%
“…The phenomenon of over- and under-cutting of the workpieces can also be avoided by a constant normal force. 21,26 In Figure 3, the comparison schematic of constant and non-constant force grinding is demonstrated. The little angle α represents the error between actual surface of workpiece and theoretical trajectory.…”
Section: Constant Force Grindingmentioning
confidence: 99%
See 2 more Smart Citations
“…Grinding and polishing with flexible-base abrasive tools are widely used processes in the aerospace, automotive, shipbuilding, bearing, tool, wood pulp, and paper industries [ 1 , 2 , 3 , 4 ]. During rough machining, these technological processes ensure the removal of significant stock allowances (up to 400 mm 3 /mm·s) [ 5 , 6 ].…”
Section: Introductionmentioning
confidence: 99%